Islamic Business Ethics Implementation Towards Sustainibility Of The Hajj And Umrah Business Travel Agency Of Makassar City - Nurbayani Nurbayani; Muliana Muliana (Universitas Islam Negeri Alauddin Makassar, 2021)
Islamic business ethics implementation could control every business activity. This research was conducted to analyze and confirm how the Islamic business ethics implementation in realizing Hajj loyalty and business sustainibilty of Hajj and Umrah travel agencies in Makassar city. This research was a direct research using a quantitative approach, and used Structural Equation Modeling (SEM) as analysis tool which is PLS (Partial Least Square) in analyzing the effect of the Islamic business ethics implementation toward business sustainibility. The results of the research found that travel agency managers had implemented Islamic business ethics in operating its operational activities including the oneness, the justice, the responsibility and the truth principle which were quite high so it was able to realize business sustainibility or the existence of a travel agency for Hajj and Umrah Makassar city, especially those whom became sample in this study. The results of this research were very encouraging information for the Hajj and Umrah in Makassar city.